Starch hydrolysates from snack scrap by starch modification method - Garalde, Victoria Ll.; Alabastro, Estrella F.
To utilize the scrap or corn curl rejects of corn puff manufacture, the starch component of the rejects was converted to hydrolyzates by starch modification methods, namely acid-modification, dextrinization and pre-gelatinization. Acid-modified starch gave the highest DE value, or the greatest extent of starch hydrolysis. Starch hydrolysis rendered the high-DE converted products, namely acid-modified and dextrinized starches less viscous, more fluid and with lower gelling properties in solution. Low-viscosity or fluid starches, as acid-modified starch, was blended with pure glucose syrup to get the desired for film-coating operations (at ratio of which favors low glucose consumption, 50:50), and used as a coat for corn curls. The glucose-converted starch blend gave high acceptability scores and enhanced texture, as revealed by sensory evaluation using paired comparison tests with pure glucose syrup at 40°B. The use of glucose-converted starch blend as a flim-coating for corn curls is thus a possible means of utilizing snack rejects.
Thesis (B.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Starch; Corn-starch.; Recycling (Waste, etc.); Snack foods